Angiographic Profile among Patients with Acute Coronary Syndrome in Tertiary Care Centre: A descriptive cross-sectional study - Regmi, Shyam Raj; Hussain, Asraf; Dhital, Bishnu Mani; Kurmi, Ram Narayan; Shah, Dhiranjan Kumar (Nepalese Heart Journal, 2026)
Background: The number of coronary arteries involved, the degree of stenosis, and the type of vessel involvement in patients with acute coronary syndrome determine presentation, morbidity and mortality. We aimed to determine angiographic findings in patients with acute coronary syndrome outside Kathmandu Valley. The data regarding angiographic profiles of patients undergoing coronary angiograms outside the valley is limited. This study aims to narrow the gap. Methods: A Descriptive cross-sectional study was conducted in the Unit of Cardiology, Department of Internal Medicine from January 1, 2022, to December 30, 2022, after ethical approval from the Institutional Review Committee (reference number:079/080-161). Convenience sampling was used. Point estimates and 95% confidence intervals were calculated. Results: Among 192 patients, majority of the patients were male with a mean age of 61.29 ± 12.50 years. Triple vessel disease (TVD) was present in 77 (40.10%) patients. Left anterior descending artery (LAD) was most involved which was present in 157 (81.77%) patients. ST-elevated myocardial infarction (STEMI) was present in 134 (69.79%) patients. Diabetes mellitus was present in 122 (63.54%) patients, and it was the most common risk factor. Conclusions: In our study, triple vessel disease and involvement of the left anterior descending artery were the most common angiographic findings. Diabetes mellitus was the most common modifiable risk factor, which could be the reason for multiple vessel involvement.